Multiplex real-time PCR for the detection of Clavibacter michiganensis subsp. michiganensis, Pseudomonas syringae pv. tomato and pathogenic Xanthomonas species on tomato plants. - Eliška Peňázová; Miloň Dvořák; Lucia Ragasová; Tomáš Kiss; Jakub Pečenka; Jana Čechová; Aleš Eichmeier (PLoS ONE)
A multiplex real-time PCR method based on fluorescent TaqMan® probes was developed for the simultaneous detection of the tomato pathogenic bacteria Clavibacter michiganensis subsp. michiganensis, Pseudomonas syringae pv. tomato and bacterial spot-causing xanthomonads. The specificity of the multiplex assay was validated on 44 bacterial strains, including 32 target pathogen strains as well as closely related species and nontarget tomato pathogenic bacteria. The designed multiplex real-time PCR showed high sensitivity when positive amplification was observed for one pg of bacterial DNA in the cases of Clavibacter michiganensis subsp. michiganensis and Pseudomonas syringae pv. tomato bacteria and 100 pg for bacterial spot-causing xanthomonads. The reliability of the developed multiplex real-time PCR assay for in planta detection was verified by recognition of the target pathogens in 18 tomato plants artificially inoculated by each of the target bacteria and tomato samples from production greenhouses.